Conserving tigers beyond protected area boundaries: the spatial ecology of tigers and their prey in farmlands in north India - Warrier, Rekha, author; Noon, Barry, advisor; Bailey, Larissa, committee member; Crooks, Kevin, committee member; Teel, Tara, committee member (Colorado State University. Libraries, 2019)
To view the abstract, please see the full text of the document.
Keywords: farmland; India; tiger; human-wildlife conflict; conservation; land-sharing